Ship-Bored - Street, Julian, 1879-1947 (Salt Lake City, UT : Project Gutenberg, 2008)
"Ship-Bored" by Julian Street is a humorous travel narrative written in the early 20th century. This book delves into the experiences and inner thoughts of a passenger aboard a transatlantic liner, offering a satirical look at sea travel and the characters encountered on board. It paints a vivid picture of the trials and tribulations faced by travelers, particularly those who struggle with seasickness. The story unfolds through the perspective of the narrator, who openly admits his disdain for the sea and finds himself battling against the malaise of boredom that accompanies long ocean voyages. The ship becomes a microcosm of society, featuring a diverse array of characters, including the cheerful but annoying passengers, the haughty socialites, and the charming entertainers. As the narrator observes the antics of fellow travelers and their amusing reactions to the hardships of sea life, he provides witty commentary on the absurdities of the voyage, culminating in comical events such as ship concerts and encounters with the ever-watchful customs spotter. Ultimately, "Ship-Bored" captures the essence of both sea travel and human eccentricity with humor and wit. (This is an automatically generated summary.)
Release date is 2008-02-11
E-text prepared by Chris Curnow, Joseph Cooper, Janet Blenkinship, and the Project Gutenberg Online Distributed Proofreading Team
Keywords: Ocean travel